Short-term exchange-rate effects of capital flows in a small open economy with pure exchange-rate targeting: Empirical evidence from Denmark's recent exchange-rate history 1984-2004 - Kim Abildgren (Danmarks Nationalbank, 2007)
Utilising a unique data set on monthly private cross-border portfolio gross and net flows to and from Denmark 1984-2004 the paper analyses the short-term relationship between capital flows related to portfolio investments and changes in the Danish nominal krone rate vis-à-vis the euro (D-mark prior to 1999). The main finding is that portfolio investments are important to short-term exchange-rate determination and that the sign of the estimated effect is as expected: Net inflows of capital strengthen the exchange rate. This result is robust to divisions of the data sample into sub-periods as well as to the inclusion of central-bank interventions in the foreign-exchange market and changes in the short-term interest-rate spread vis-à-vis the currency anchor as endogenous explanatory variables. Portfolio flows in Danish bonds appear to be driving the results prior to the introduction of the euro. Since then the main driver has been portfolio investments in foreign shares. Over time there appears to have been a declining effect on the krone-rate from portfolio flows which might be seen as the result of increased credibility of the Danish exchange-rate peg.
Keywords: E52; F31; F32; 330; Portfolio flows; FX microstructure; Exchange-rate dynamics; Portfolio-Investition; Kapitalmobilität; Monetäre Wechselkurstheorie; Regression; Dänemark